Using Low-Interaction Honeypots to Study the Abuse of Open Proxies to Send Spam - Steding-Jessen, Klaus; Vijaykumar, Nandamudi L.; Montes, Antonio (INFOCOMP Journal of Computer Science, 2008)
One of the main problems in creating effective mechanisms to mitigate the spam problem is the lack of more precise data on it. This paper describes the design and implementation of a honeypotbased architecture to study the abuse of open proxies to send spam. The sensors were installed in Brazilian broadband networks and they captured more than 500 million emails over a period of 15 months. In this paper we present the analysis of these data and describe some contributions to the spam capture field that were implemented.